A Special Fiber Optic Sensor for Measuring Wheel Loads of Vehicles on Highways - Norman W. Garrick (Sensors, 2008)
This paper presents results from an investigation on a special optical fiber as a load sensor for application in Weigh-in-Motion (WIM) systems to measure wheel loads of vehicles traveling at normal speed on highways. The fiber used has a unique design with two concentric light guiding regions of different effective optical path lengths, which has the potential to enable direct measurement of magnitudes as well as locations of forces acting at multiple points along a single fiber. The optical characteristic of the fiber for intended sensing purpose was first assessed by a simple fiber bending experiment and by correlating the bend radii with the output light signal intensities. A simple laboratory load transmitting/fiber bending device was then designed and fabricated to appropriately bend the optical fiber under applied loads in order to make the fiber work as load sensor. The device with the optical fiber was tested under a universal loading machine and an actual vehicle wheel in the laboratory. The test results showed a good relationship between the magnitude of the applied load and the output optical signal changes. The results also showed a good correlation between the time delay between the inner and outer core light pulses and the distance of the applied load as measured from the output end of the fiber.